An inheritance of ashes a novel - Bobet, Leah (Clarion Books, 2015)
Now that the strange war is over, sixteen-year-old Hallie and her sister struggle to maintain their family farm, waiting to see who will return from the distant battlefield, soon hiring a veteran to help them but, as ugly truths about their family emerge, Hallie is taking dangerous risks and keeping desperate secrets while monsters and armies converge on the small farm